The era of post-war prosperity and the Great Depression, 1920-1936 - Foner, Philip Sheldon, 1910-1994; Lewis, Ronald L., 1940-; Ervin, Keona K. (Black worker, 2019)
"The work of notable Black labor scholars in addition to Du Bois, finds a home in the middle volumes. For example, George E. Haynes, the first African American man to earn a Ph.D. from Columbia University and Director of Negro Economics for the United States Department of Labor, and Helen B. Irvin, an expert on Black women's labor, have writings that yield social-scientific insight. On the subject of Black women's labor history, volume six includes a rich collection, with studies on Black women industrial workers in Philadelphia from the U.S. Department of Labor and articles written by labor intellectuals including Helen Sayre, Mary Louise Williams, Nora Newsome, and Jean Collier Brown for publications such as the National Urban League's Opportunity and The Messenger, as well as for the Women's Bureau. The Brotherhood of Sleeping Car Porters has voluminous records dedicated to it. Numerous articles from The Messenger, The New Leader, The Chicago Defender, The Pittsburgh Courier, and records from the Chicago Historical Society capture the work of the historic Black-led labor union of Pullman Porters"--From foreword.